2020
DOI: 10.5194/aab-63-423-2020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of genotype and muscle type on the physico-chemical characteristics and taurine, carnosine and L-carnitine concentration in lamb meat

Abstract: Abstract. An experiment was conducted to determine the chosen bioactive components and physico-chemical characteristics of lamb meat of different animal genotypes and the muscle types. The 22 ram lambs of Polish Merino (PM) and 22 crossbreeds of Polish Merino × Berrichone du Cher (PMB) were fattened to achieve their slaughter weight of 40 kg. After slaughter, the carcasses were kept at 4 ∘C for 24 h. Then, the samples of longissimus lumborum (LL) and gluteus medius (GM) muscle were collected to analyse the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
(37 reference statements)
2
5
0
1
Order By: Relevance
“…The effect of muscle type on meat color was not recorded by the authors in their previous study on Polish Merino lambs in fresh meat, while after 14 days of aging, the L* value in longissimus lumborum muscle was significantly higher compared to GM muscle [38]. However, in another study conducted by the authors on fresh meat from Polish Merino lambs and Polish Merino x Berrichone du Cher crossbred lambs, higher L*, lower b* and H* values were determined in the GM muscle of both tested genotypes [5]. The variation in the values of parameters determining meat color was also indicated by Realini et al [39] when analyzing the relationship between meat quality and muscle type and their morphological structure in pigs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The effect of muscle type on meat color was not recorded by the authors in their previous study on Polish Merino lambs in fresh meat, while after 14 days of aging, the L* value in longissimus lumborum muscle was significantly higher compared to GM muscle [38]. However, in another study conducted by the authors on fresh meat from Polish Merino lambs and Polish Merino x Berrichone du Cher crossbred lambs, higher L*, lower b* and H* values were determined in the GM muscle of both tested genotypes [5]. The variation in the values of parameters determining meat color was also indicated by Realini et al [39] when analyzing the relationship between meat quality and muscle type and their morphological structure in pigs.…”
Section: Discussionmentioning
confidence: 61%
“…Many studies have shown that breed, age at slaughter, the feeding system and related muscle development and the proportion of different types of muscle fibers determine important meat characteristics for the consumer, such as color, tenderness, juiciness or intramuscular fat content, as well as the presence of biologically active ingredients [3][4][5][6][7][8][9][10][11]. The quality of the meat is also affected by physiological, biochemical and metabolic changes that occur during meat aging.…”
Section: Introductionmentioning
confidence: 99%
“…Taurine is one of the most abundant amino acids that exist in organism in free state. For example, taurine concentrations in breast and thigh muscle tissues of broilers are 10.4 and 165.5 mg/100 g tissue, respectively ( Huang et al., 2014 ), which is comparable to that in skeletal muscle of lamb (59.9–75.5 mg/100 g, Radzik-Rant et al., 2020 ) and rats (17–33 μmol/g wet tissue, Iwata et al., 1986 ). TAU can be synthesized from Met in chicken ( Martin, 1972 ).…”
Section: Discussionmentioning
confidence: 95%
“…Es importante considerar, que en general dentro de los factores que afectan el color de la carne, se encuentra el genotipo, la alimentación y la edad (34), con una tendencia hacia el incremento de la cantidad de pigmentos y el índice de rojo (a*), así como la disminución de la luminosidad a medida que aumenta la edad (L*).…”
Section: Característicasunclassified